Peripheral Inotropes in Critically Ill Children: Is It Safe? - Ravi K. Mooli MBBS, MD; Kalaimaran Sadasivam MBBS, DCH, MRCPCH (SAGE Publishing, 2021)
Many children needing pediatric intensive care units care require inotropes, which are started peripherally prior to securing a central venous access. However, many hospitals in low- and middle-income countries (LMIC) may not have access to central lines and the vasoactive medications are frequently given through a peripheral venous access. Aim : The aim of our study was to describe the role of peripheral vasoactive inotropes in children. Methods : Children requiring peripheral vasoactive medications were included in this study. We retrospectively collected data at 2 time points on use and complications of peripheral vasoactive medications. Results : Eighty-four children (51 pre-COVID era and 33 COVID pandemic) received peripheral vasoactive medications. Only 3% of children (3/84) developed extravasation injury, all of whom recovered completely. Conclusions : Results from our study suggest that extravasation injury due to peripheral inotrope infusion is very low (3%) and it may be safely administered in children at a diluted concentration.